SOSIALISASI DAN PELAKSANAAN ALL STARS KINDERGARTEN SPORTS FESTIVAL - Hatena Manopo, Boyke Adam; Tahki, Kurnia; Dewanti, Rina Ambar; Aryati; Antoni, Rizka (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Early age is the age when children begin to recognize themselves and the environment around them, therefore at this time, children must be given various stimuli or stimuli so that their growth and development is good. Early childhood education is a coaching effort aimed at children from birth to 6 years of age which is carried out by giving educational stimuli to help the physical and spiritual growth and development of children in preparation for life and can adapt to their environment and have readiness to enter further education. Age 4-6 years is a mature age for early childhood to maximize movement activity, and physical fitness. Therefore, this service aims to socialize basic movement activities to carry out early childhood sports festival activities with the theme